Professional Pathways of Educators of Educators: An Argentine-French study on identity, recognition and professionalization with an impact on employability - Aparicio, Miriam Teresita (2021)
Researchers around the world analyze the pathways of university educators and educators from Institutes of Teacher Formation, pathways which are conditioned by history and marked by the influence of context and the abrupt changes which have taken place recently. All of this together affects both teacher identity and employability. Our sample was made up of teachers from different levels, institutions, environments, provinces and from three different countries. In this work, we will compare findings from Institutes of Teacher Formation (IFD) in Argentina (Cuyo region) with those of institutes in France (IUFM from East Paris–Créteuil, France). This will allow us to capture contextual differences as they affect the level of objective achievement and satisfaction. The model includes base, sociocultural, psychosocial, organizational and structural factors. Our methodology was quanti-qualitative (lexicometric analysis and interviews). This allowed us to understand the central issue that each study program itself has and how it relates to the working world, as well as the distances between the prescribed world and the real world of these actors. We also applied a semi-structured survey with open-ended answers, which permitted us to utilize the technique of hierarchical evocation. The results show shared representations of teachers at the tertiary level in Argentina and France, illustrating strengths and weaknesses particularly regarding weakening recognition and global devaluation of teachers. The results will be presented to decision makers in education with aims to implement programs of Professionalization which could overcome the aspects that today fracture identities and create upset among teachers, impacting their employability.